From the Grand Tour to the Grand Hotel: The Birth of the Hospitality Industry in the Grand Duchy of Tuscany between the 17th and 19th Centuries. Issue 1 (18th April 2018) - Susini, Fabiana
Abstract : This article investigates the architecture of different types of accommodations in the Grand Duchy of Tuscany between the 17th and early 19th centuries. Buildings used as paid accommodation facilities such as inns, hotels, and guest houses were utilitarian buildings that reflected the tastes of their time and the customs and rituals related to travel, and thus had particular architectural features. This work proposes an analysis of the architectural properties of those accommodation facilities as well as their environmental and historical contexts and the transformations they have undergone through time. With this in mind, I look at the development of two types of accommodations in particular that are representative of Tuscany: coaching inns, which often replaced earlier medieval inns and were the focal point of the Grand Duchy's accommodation system for travellers; and city hotels, rooms usually located inside ancient, privately owned palaces converted to accommodate visitors.